Molecular typing and virulence markers of Yersinia enterocolitica strains from human, animal and food origins isolated between 1968 and 2000 in Brazil - Falcao, Juliana P.; Falcao, Deise P.; Pitondo-Silva, Andre; Malaspina, Ana Carolina; Brocchi, Marcelo (Soc General Microbiology, 2006)
Molecular typing and virulence markers were used to evaluate the genetic profiles and virulence potential of 106 Yersinia enterocolitica strains. of these strains, 71 were bio-serotype 4/O: 3, isolated from human and animal clinical material, and 35 were of biotype 1 A or 2 and of diverse serotypes, isolated from food in Brazil between 1968 and 2000. Drug resistance was also investigated. All the strains were resistant to three or more drugs. The isolates showed a virulence-related phenotype in the aesculin, pyrazinamidase and salicin tests, except for the food isolates, only two of which were positive for these tests. For the other phenotypic virulence determinants (autoagglutination, Ca++ dependence and Congo red absorption), the strains showed a diverse behaviour. The inv, ail and ystA genes were detected in all human and animal strains, while all the food isolates were positive for inv, and 3% of them positive for ail and ystA. The presence of virF was variable in the three groups of strains. The strains were better discriminated by PFGE than by enterobacterial repetitive intergenic consensus PCR (ERIC-PCR). A higher genomic similarity was observed among the 4/O: 3 strains, isolated from human and animal isolates, than among the food strains, with the exception of two food strains possessing the virulence genes and grouped close to the 4/O: 3 strains by ERIC-PCR. Unusually, the results revealed the virulence potential of a bio-serotype 1 A/O: 10 strain, suggesting that food contaminated with Y. enterocolitica biotype 1 A may cause infection. This also suggests that ERIC-PCR may be used as a tool to reveal clues about the virulence potential of Y. enterocolitica strains. Furthermore, the results also support the hypothesis that animals may act as reservoirs of Y. enterocolitica for human infections in Brazil, an epidemiological aspect that has not been investigated in this country, confirming data from other parts of the world.